PENGARUH LEMBAR KERJA PESERTA DIDIK BERORIENTASI INKUIRI TERBIMBING TERHADAP KOMPETENSI IPA KELAS VII SMPN 2 BUKITTINGGI - Betty Mizarwan; Ratnawulan Ratnawulan; Gusnedi Gusnedi (Universitas Negeri Padang, 2015)
Learning science by 2013’s curriculum one of them is using inquiry learning model that comes with the use of teaching materials such as students worksheet in accordance with the syntax of the learning model. Students Worksheet that exist in schools does not yet support teacher learning model chosen optimally, because whatever the chosen learning model teacher the book remains is same. Therefore conducted a study to investigate the effect of guided inquiry-oriented students worksheet towards science competency of VII’s class SMPN 2 Bukittinggi on inquiry learning model with guided inquiry method. The research is a quasi-experimental design with posttest only control design on two groups of randomly selected classes. The population in this study is all of VII’s classes SMPN 2 Bukittinggi enrolled in the academic year 2014/2015. Sampling using cluster random sampling. Samples are VII.4’s class as an experimental class and control class is VII.5’s class. Data collection techniques for competency attitude using non-test techniques, using technical knowledge competency test, and competence skills in using non-test techniques. Analysis of the data is done by testing the equality of two average. IPA competence students experimental class average rating is better than the control class. The average value of competence attitudes, knowledge, and skills in sequence for the experimental class 82.20; 83.46; and 78.90 and 77.10 for the control class; 78.70; and 71.90. After testing the equality of two average there are significant differences between the experimental class with a third control class in the realm of competence. It can be concluded that the use of guided inquiry-oriented students worksheet have an influence on the science competency of class VII SMPN 2 Bukittinggi on the real level of 0.05